Characterization and effects of halloysite nanotubes and date palm fibers on thermoplastic starch based nanocomposites - Aboelsoud, Ahmed Mostafa (AUC Knowledge Fountain, 2019)
Great attention was paid to develop new eco-friendly “green” materials with growing environmental awareness in recent years. Composites of environmental friendly reinforcements and resins that provide high performance at affordable costs are in continuous progress. In this work, completely biodegradable thermoplastic starch (TPS) based matrix was reinforced with Halloysite nanotubes (HNTs) and date palm fibers (DPFs) individually with different HNTs weight fractions (2.5 to 10 wt. %) in order to investigate their effect on composite mechanical properties. HNTs and DPFs were then combined to reinforce TPS- based matrix at the optimum fiber weight content. Thermoplastic starch (TPS) was obtained by blending native corn starch with glycerin and water. The plasticized starch was emulsified before being added to the previously bleached and NaOH-treated date palm fibers. The composites were preheated and then hot pressed at 5 MPa and 160oC for 30 minutes. FTIR spectra showed the increase in hydrogen bonds formation to all HNTs and DPFs composites. FE-SEM investigation showed strong adhesion at HNTs and fiber-matrix interface and good fibers wettability. Static tensile and flexural mechanical properties (stiffness and strength) of the composites appeared to markedly increased with the HNTs fraction increase until 7.5 and 5 wt. % for HNTs/TPS nanocomposites and HNTs/DPFs/TPS nanocomposites respectively. Also the composite stability was improved in thermal degradation, water uptake tests by the addition of HNTs and increasing its content. The results showed that composites mechanical properties improved by adding HNTs until certain wt. % content because above it the HNTs aggregate and adversely affect the mechanical properties. Such nanocomposites have competitive properties, qualifying these materials to be inexpensive and appropriate alternatives for various applications.